Anxiety in nurses during the COVID-19 pandemic - dos Santos Assis , Carolaine; Shamara Silva França, Thaina (Seven Editora, 2023)
Introduction: With the COVID-19 pandemic, public and private emergency services have been suffering from overcrowding, increased work rate, and an overload of health professionals, making physical, material, and human resources scarce. Objective: To identify in the literature scientific evidence about anxiety in nursing professionals during the Covid-19 pandemic. Method: This was a narrative review, which used the online interface of the Virtual Health Library (VHL), using the descriptors "Anxiety"; "Covid-19;"; "Nurses." After searching the databases, 81 articles were found that underwent a reading of the title and abstract, 15 articles were selected for full and critical reading and all were considered eligible for the work. Results: Health professionals suffered great physical and psychological stress during the COVID-19 pandemic, with a high prevalence of anxiety among nurses, especially in women. The increased workload, fear of contracting and transmitting COVID-19, uncertainties about the disease, the lack of personal protective equipment were the factors that contributed to the anxiety of the professionals. The auriculotherapy technique was cited as a way to promote anxiety relief. Conclusion: It is necessary to verify other methods and strategies of support to reduce the factors that trigger the physical and psychological suffering of the professional, providing basic supply and subsidies for the safety of the team of nursing. DOI: https://doi.org/10.56238/devopinterscie-176